An Analysis Translation Slang Language Based on TikTok Content at The Fifth Semester Students of English Education Department Universitas Islam Madura - Sa'adah, Khalifatus; Yunitaka Bahrudin, Dinar Vincy; Jaftiyatur Rohaniyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to analyze the strategy of translating English slang based on TikTok content by fifth semester students of English Education Department Universitas Islam Madura. Using a qualitative case study approach, data were collected through a translation worksheet and semi-structured interviews with 23 students. Ten slang words from TikTok were chosen as translation material. The results showed that the most dominant strategy used was equivalence, where students tended to choose the appropriate meaning in the target culture, such as translating "you bet" to "pasti" or "oke", and "slay" to "memukau". Other strategies such as adaptation, expansion, and free translation are also used according to context. However, mistakes are still found, especially when students translate literally, such as "pick me" into "choosing me", which causes the meaning is not right. From the results of the interview, the main obstacles in translating slang are idioms and cultural references, as well as the cultural distance between the source language and the target.  This research shows the importance of cultural awareness and bilingual ability to translate slang contextually and effectively.